The role of education in supporting village women's empowerment in Aceh in the context of local social, religion, and culture - Zulkarnaini, Zulkarnaini; Sufyan, Muhammad Suhaili; Miswari, Miswari; Fakhrurazi, Fakhrurazi (Educenter : Jurnal Ilmiah Pendidikan, 2024)
This study aims to explore the role of education in supporting women's empowerment in rural Aceh, understand the challenges they face, and see how education can be a tool to strengthen their position in the social structure without bumping up against traditional and religious values. Through a qualitative approach, this study explores the main factors that influence women's access to and participation in formal and non-formal education, including socio-cultural and economic barriers. This conceptual model identifies key components such as the role of local educational institutions, local values (such as mutual cooperation and religious teachings), and community and family support in improving access to education for women. The findings show that education has an optimal impact on women's involvement in social and economic life, allowing them to play a greater role outside the domestic sphere. However, various challenges such as conservative views and the lack of inclusive policies are still obstacles. With the existence of supportive policies and the integration of local values in education, it is hoped that women's empowerment in Aceh can be realized sustainably. This study is expected to contribute to the formulation of more inclusive education policies for women in rural Aceh.